Ventriculo-peritoneal shunt malfunction due to complete migration and subgaleal coiling of the proximal and distal catheters. Issue 1 (January 2015) - Pikis, Stylianos; Cohen, José E.; Shoshan, Yigal; Benifla, Mony
Abstract Ventriculo-peritoneal (VP) shunt malfunction due to proximal and distal catheter migration has been rarely reported in the literature. Shunt migration has been proposed to occur as a result of a combination of various mechanisms, including the windlass effect, retained memory of the shunt tubing, inadequate shunt fixation, and increased intra-abdominal pressures. We describe a rare case of a 6-week-old child who presented in our department with VP shunt malfunction due to complete proximal migration and coiling of the peritoneal and ventricular VP shunt catheters within a subgaleal pocket at the left occipital area.